Early diagnosis of pancreatic adenocarcinoma: role of stroma, surface proteases, and glucose-homeostatic agents - Fric, Premysl; Zavoral, Miroslav (Pancreas, 2012)
OBJECTIVES: New-onset diabetes in pancreatic adenocarcinoma is due to a combination of insulin resistance and decreased β-cell function. Its differentiation from the common type 2 diabetes is the prerequisite for early diagnosis of pancreatic adenocarcinoma. Little attention has been paid to pancreatic stroma and surface proteases. METHODS: The activated fibroblasts selectively express fibroblast activation protein α, a structural homolog of the ubiquitously expressed dipeptidyl peptidase 4. Their role in pancreatic carcinogenesis is reviewed. RESULTS: Homodimers and heterodimers of both enzymes display high specificity for peptides and proteins with penultimate proline or alanine. Most glucose-homeostatic agents are candidate substrates of these enzymes. The biological activity of truncated substrates is decreased or absent. CONCLUSIONS: The interactions of surface proteases with glucose-homeostatic agents may adequately explain the evolution of diabetes associated with pancreatic adenocarcinoma and differentiate it from the common type 2 diabetes.
Keywords: serinové endopeptidasy; Serine Endopeptidases; Dipeptidyl Peptidase 4; endopeptidasy; Diabetes Mellitus, Type 2; Pancreatic Neoplasms; beta-buňky; lidé; glukagonu podobný peptid 1; dipeptidylpeptidasa 4; nádory slinivky břišní; membránové proteiny; diabetes mellitus 2. typu; časná diagnóza; Endopeptidases; Adenocarcinoma; glukosa; adenokarcinom; Glucose; Insulin-Secreting Cells; želatinasy; Glucagon-Like Peptide 1; Early Diagnosis; Membrane Proteins; Gelatinases; Humans